Production and grazing utilization of Medicago arborea by Sarda ewes and their performance in an extensive grazing system - Salis L.; Acciaro M.; Decandia M.; Giovanetti V.; Molle G.; Sitzia M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
A crop of 1000 seedlings (25-30 cm in height) of the shrub Medicago arborea was established in spring 2017 in the experimental farm of Bonassai (N-W Sardinia, Italy) to study its forage production and nutritive value in Sarda sheep grazing system. Plants were transplanted at 1 m from each other in rows 4 m apart (2500 plant ha-1). In 2018, plant height and diameter were measured, monthly. In July 2018 and in January 2019 (grazing periods) a plot (3500 m2) of M. arborea was grazed by 24 mature Sarda dairy ewes for 14 days. Before the beginning and after the end of each grazing period, the available edible biomass (dry matter) and its nutritive value were evaluated. All ewes were supplemented with concentrate and hay. Animal performance was assessed three times during each grazing period, at the beginning (Beg), the middle (Mid) and the end (End). Available edible biomass was 604 ±40 and 526 ±26 kg ha-1 in July and January, respectively. Crude protein content was always greater than 150 g kg-1 DM. In both grazing periods, the ewes ingested more than 80% of the available crop edible biomass. The body weight and body condition score of ewes did not change between Beg and End of grazing. Daily milk production decreased at the end of the grazing period due to a reduced dry matter availability. Milk fat, protein, and casein did not significantly change between Beg and End of grazing. To conclude, M.arborea could contribute to cover dairy sheep requirements during periods of herbage shortage.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)